PERBANDINGAN HUKUM TERHADAP STATUS ANAK HASIL ZINA, PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF - Zidan Fauzan, Muhammad; Ipin Tajul Aripin (Ahwaluna | Jurnal Hukum Keluarga Islam, 2025)
The objectives to be achieved in this study are: 1) Analyze the status of children resulting from adultery in Islamic law, 2) Analyze the positive legal view on children resulting from adultery, 3) Determine the consequences of children resulting from adultery in population administration. This research method uses a qualitative descriptive design. That is, presenting in the form of descriptions. The author uses a theological approach, a juridical approach, and a sociological approach in collecting data. The data collection technique used is the library research method. Data processing and analysis techniques are deductive, inductive, and comparative.The results of the study concluded that: 1) The status of out-of-wedlock children in positive law is that out-of-wedlock children do not have a civil relationship either with the mother who gave birth to them or with the man who impregnated their mother, if both have not or do not admit it. An out-of-wedlock child has a civil relationship with the mother who gave birth to him, if he admits it. Or with the man who impregnated his mother who admitted it, or with both who had admitted it. And the child out of wedlock becomes a legal child, that is, an out-of-wedlock child who is recognized by the mother who gave birth to him and the father who seeded him and followed by their marriage. . 2) The status of an out-of-wedlock child in Islamic law is that the child does not have a nasab relationship with his father, but has a nasab relationship with his mother. The father has no obligation to provide for the child, but is biologically his child. So the relationship that arises is only humanely, not legally, not inheriting property with the father, because the relationship of nasab is one of the causes of inheritance. And the father cannot be the guardian of the child out of wedlock. If an out-of-wedlock child happens to be a woman and is an adult and will marry, then he is not entitled to be married by his biological father. 3) The consequences of children resulting from adultery in civil administration can still be resolved if the child resulting from adultery is recognized and can be reported to his parents Keywords: Children Out of Wedlock, Positive Law and Islamic Law